Workplace favouritism, psychological contract violation and turnover intention: Moderating roles of authentic leadership and job insecurity climate - Arasli, Huseyin; Arici, Hasan Evrim; Arici, Nagihan Cakmakoglu (Sage Publications Inc, 2019)
The multilevel investigation examines the impacts of favouritism on non-beneficiaries' turnover intention by focusing on the mediating role of psychological contract violation and the moderating roles of job insecurity climate and authentic leadership in family firms. Congruent with the theories of relative deprivation, belongingness, and social identity, this paper is among the first to propose and empirically examine how and when favouritism leads to higher or lower turnover intention in family firms. Having utilized time-lagged data from 576 non-beneficiaries who came from 101 work groups in 48 family firms in Turkey, our findings support the following: the significance of favouritism by demonstrating that non-beneficiaries' turnover intentions are higher in family firms when they perceive favouritism to be high; favouritism in family firms positively influences psychological contract violation; psychological contract violation acts as a mediator of the association between favouritism and non-beneficiaries' turnover intention; and both job insecurity climate and AL act as moderators of the relationship between favouritism and turnover intention. The theoretical and practical contributions of these findings are discussed.
Keywords: favouritism; psychological contract violation; turnover intention; authentic leadership; job insecurity climate; human resource management; family firms